Widder- und pferdeförmige Grabsteine: ein religions- und völker-übergreifendes Phänomen - Schürr, Diether (ARAMAZD: Armenian Journal of Near Eastern Studies, 2024)
Tombstones in the shape of rams or horses are a widely distributed phenomen mainly in the East of Turkey and the adjacent states, used by people of differing religious and ethnic affiliation: by Christians, Shiites, Alevites, and Yazidis but probably not Sunnis, by Georgians, Armenians, Aramaeans, Kurds, Zazas, possibly the Talysh, non-Ottomanian Turks or Türkmens, perhaps also Ottomanian Turks. The extremes are a group of rams in central Anatolia north of Afyon, and rams on the north-east side of the Caspian Sea in Kazakhstan. They are mostly of post-medieval date, and none can be reliably dated earlier, as far as I can see. This is only an initial, provisional collection of the information available, beginning with early travelersʼ reports since 1818, because tombstones of that kind are understudied, and their treatment in Turkish and Azerbaijani publications is hampered by ideology.